On the performative character of Nakba in Edward Said’s ultimate thought. Implications for his understanding of domination, struggle and liberation of the Palestinian people - Rodríguez Fernández, Judit (Anaquel de Estudios Árabes, 2024)
This article analyzes the notion of Nakba in Edward Said’s thought between the signing of the Oslo accords in 1993 and his death in 2003. Although he did not elaborate any work where he specifically expounded his understanding of Nakba, it pervaded most of his writings. Thus, our aim is twofold: to examine how his understanding of the Nakba transformed as political events in Palestine unfolded; and to investigate whether he articulated an understanding of domination, struggle and liberation with claims to intervening in the present. To this end, we will analyze his works, essays, articles and interviews in the light of Koselleck’s conceptual history and Walter Benjamin’s concept of “experience”. The latter allows us to unleash the revolutionary potential of the Nakba as a collective experience by transcending the understanding that makes it just another historical event, and the former reveals its performative character. From here we will approach the Saidian writings seeking to know whether Said offers a reflection of the Nakba that entails a practical dimension capable of offering the Palestinian people an experience liberated from Zionist domination. However, we will conclude that the terms in which Said formulates it prevent the Nakba from unleashing its liberatory potential.